Socioeconomic inequalities in self-reported health and physical functioning in Argentina: findings from the national survey on quality of life of older adults 2012 (ENCaViAM) - Rodríguez López, Santiago (2017)
This study aimed to evaluate educational and income inequalities in self-reported health (SRH), and physical functioning (limitations in Activities of Daily Living (ADL)/Instrumental Activities of Daily Living (IADL)), among 60-year-old and older adults in Argentina. Using cross-sectional data from the Argentinian National Survey on Quality of Life of Older Adults 2012 (Encuesta Nacional sobre Calidad de Vida de Adultos Mayores, ENCaViAM), gender-specific socioeconomic inequalities in SRH and ADL and IADL limitations were studied in relation to educational level and household per capita income. The Relative Index of Inequality (RII) - an index of the relative size of socioeconomic inequalities in health - was used. Socioeconomic inequalities in the studied health indicators were found - except for limitations in ADL among women - favouring socially advantaged groups. The results remained largely significant after full adjustment, suggesting that educational and income inequalities, mainly in SRH and IADL, were robust and somehow independent of age, marital status, physical activity, the use of several medications, depression and the occurrence of falls. The findings add to the existing knowledge on the relative size of the socioeconomic inequalities in subjective health indicators among Argentinian older adults, which are to the detriment of lower socioeconomic groups. The results could be used to inform planning interventions aimed at decreasing socioeconomic inequalities in health, to the benefit of socially disadvantaged adults.